Assessing models for estimating future forest biodiversity and ecosystem service provision in support of Integrative Forest Management - Sina Reuter; Verena C. Griess; Jasper M. Fuchs; Volodymyr Trotsiuk; David I. Forrester; Janine Schweier; Olalla Díaz-Yáñez (Ecological Modelling, 2026)

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Experimental study on the interaction of falling films and sprays during cleaning - M. Joppa; R. Schade; T. Hanisch; C. Golla; E. Fuchs; M. Mauermann (Food and Bioproducts Processing, 2026)

Quaternary terrace formation in response to climate, regional uplift and local normal faulting: The Danube terrace staircase of Vienna - B.C. Salcher; S.M. Neuhuber; J.-C. Otto; T. Payer; C. Lüthgens; S. Fuchs; A. Flores-Orozco; J. Nørgaard; S. Grupe; O. Marchhart; A. Wieser; J. Lachner; et al. (Quaternary Science Reviews, 2026)

Correction: Seasonal and Interannual Variability of Exchange between Delaware Bay and the Continental Shelf - Gregory P. Gerbi; Elias J. Hunter; Jacqueline M. McSweeney; Heidi L. Fuchs; Robert J. Chant; Jessica C. Garwood; John Wilkin (Estuaries and Coasts, 2026)

Seasonal and Interannual Variability of Exchange Between Delaware Bay and the Continental Shelf - Gregory P. Gerbi; Elias J. Hunter; Jacqueline M. McSweeney; Heidi L. Fuchs; Robert J. Chant; Jessica C. Garwood; John Wilkin (Estuaries and Coasts, 2026)
This study of Delaware Bay, USA, uses a numerical particle tracking model to examine the exchange of material between the bay and adjacent continental shelf on seasonal timescales. Vertically averaged, near-bottom, and near-surface transport were targeted by simulating particles with three different types of behavior: neutrally buoyant, bottom-seeking (similar to silt settling), and surface-seeking (similar to the slow rise of buoyant material), respectively. Particle release locations are drawn from a space-filling distribution throughout the model domain, and the origin regions of particles that enter the bay vary seasonally, interannually, and with particle behavior. The mean along-shelf circulation is from the northeast to the southwest, and particles entering the bay tend to come from the northeast, within tens of kilometers from shore. Source regions of bottom-seeking particles that enter the bay are farther offshore than source regions of neutral or surface-seeking particles. Bottom-seeking particles also remain in the bay for longer times than particles with other behaviors. Particles of all behaviors are flushed out of Delaware Bay more quickly in winter than in summer. Although this study focuses on a specific region of eastern North America, the findings about sources of particles to the bay are likely applicable to other embayments with similar shelf circulation patterns and may guide efforts to better understand transport of pollutants, larvae, and other material.

Improvement of the antimicrobial efficacy of high-intensity blue light against Pseudomonas aeruginosa by discontinuous irradiation - Tara Fardoust; Isabell Blassnig; Paul C. Fuchs; Jennifer L. Schiefer; Christian Opländer (Journal of Photochemistry and Photobiology B: Biology, 2025)

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Attenuated but not virulent pseudorabies virus activates porcine bone marrow-derived dendritic cells - Emily C. Ashley; Walter Fuchs; Barbara G. Klupp; Dirk Werling; Simon P. Graham; Jane C. Edwards (Veterinary Immunology and Immunopathology, 2025)

Subcutaneous zilucoplan: Evaluation of reproductive toxicology - Marie Lemper; C. Marc Luetjens; Antje Fuchs; Peter Hall; François-Xavier Mathy; Jeff Long; Joy Cavagnaro; Sucharita Roy; Evan A. Thackaberry; Petra Duda (Reproductive Toxicology, 2025)

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Immunophenotype investigation in feline intestinal non-B-cell lymphoma - Birgitt Wolfesberger; Gabriele Gradner; Barbara C. Rütgen; Katharina M. Hittmair; Ingrid Walter; Taryn A. Donovan; Miriam Kleiter; Alexander Krischak; Iwan A. Burgener; Andrea Fuchs-Baumgartinger (Journal of Comparative Pathology, 2024)

Mixture toxicity study of two metal oxide nanoparticles and chlorpyrifos on Eisenia andrei earthworms - Marcela I. Cáceres-Wenzel; Florencia N. Bernassani; Julio S. Fuchs; Eduardo Cortón; Adriana C. Cochón (Environmental Science and Pollution Research, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Multi-sensor characterization for an improved identification of polymers in WEEE recycling - Andréa de Lima Ribeiro; Margret C. Fuchs; Sandra Lorenz; Christian Röder; Johannes Heitmann; Richard Gloaguen (Waste Management, 2024)

A multi-criteria drought resistance assessment of temperate Acer, Carpinus, Fraxinus, Quercus, and Tilia species - C. Leuschner; S. Fuchs; P. Wedde; E. Rüther; B. Schuldt (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Evaluating Fracture Surface Imaging Methods Using Flow Simulations and Air Permeameter Measurements - Marco Fuchs; Sina Hale; Larissa Blesch; Gabriel C. Rau; Kathrin Menberg; Philipp Blum (Rock Mechanics and Rock Engineering, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Influences of brood-dependent behavioral variation on blue crab (Callinectes sapidus) larval transport in a wind-driven estuarine plume - Joseph C. Caracappa; Daphne M. Munroe; Heidi L. Fuchs; Robert J. Chant (Ecological Modelling, 2023)

Defense response-like reaction associated with an anomaly in Eucalyptus grandis - Maria C. P. Fuchs; Bruno C. Rossini; Marcio L. Acencio; Ney Lemke; Esteban R. González; Salvatore Moricca; Tiziana Panzavolta; Edson L. Furtado; Shinitiro Oda; Celso L. Marino (Trees, 2022)

Estuarine retention of larvae: Contrasting effects of behavioral responses to turbulence and waves - Jessica C. Garwood; Heidi L. Fuchs; Gregory P. Gerbi; Elias J. Hunter; Robert J. Chant; John L. Wilkin (Limnology and Oceanography, 2022)
The intensity of small‐scale fluid motions varies among coastal seascapes, which could drive species‐specific behavioral adaptations in planktonic larvae. For example, inlets and estuaries typically have stronger turbulence and weaker surface gravity waves than the continental shelf. In the Mid‐Atlantic Bight, eastern mudsnails ( Ilyanassa obsoleta ) inhabit inlets and estuaries, whereas threeline mudsnails ( Ilyanassa trivittata ) inhabit the continental shelf. The two species' larvae respond differently to hydrodynamic signals: both hover in calm conditions and sink in response to vorticity, a signal of turbulence, while only shelf snail larvae also sink and swim up in response to accelerations, which can be large under waves. We investigated how these observed larval behaviors and more idealized ones affect retention and settlement in estuaries using numerical experiments. Virtual larvae were released and tracked in a regional model of Delaware Bay and the adjacent shelf. Behaviors that involved downward motions, including vorticity‐induced behaviors, helped concentrate larvae near the bottom and enhanced retention in the bay. In contrast, behaviors that involved upward motions, including acceleration‐induced behaviors, promoted export onto the shelf. Compared to neutral buoyancy, the vorticity‐induced behaviors also conferred longer residence times in the bay, higher settlement probabilities, and shorter pelagic larval durations, all of which would be advantageous to estuarine species. This integration of larval observations with simulations provides evidence that behavioral responses to coastal physics can reduce larval mortality by enhancing retention and settlement in native seascapes.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Designing real-world laboratories for sustainable urban transformation: addressing ambiguous roles and expectations in transdisciplinary teams - Sandra Huning; C. Räuchle; M. Fuchs (Sustainability Science, 2021)
This paper reflects upon the potential of real-world laboratories (RWLs) to promote sustainable urban development. RWLs strive for knowledge production through collective action in experimental settings. Their implementation in urban studies faces two major challenges: (1) the ambiguity of roles university researchers need to fill, and (2) the variety of expectations among team members from different institutional backgrounds. Based on research in one trans-European and three German RWLs, we propose a stronger focus on team development to help researchers in RWLs address these challenges more systematically. In particular, this means support in terms of resources and infrastructure (time, space, and training). We argue that the improvement of RWL team performance has great impact on the potentials of RWLs in transformative urban studies. Thus, the article contributes to the ongoing debate on the city as a laboratory and site of experimentation in times of multiple crises.

Construction and use of rock-cut cisterns: a chronological OSL approach in the arid Negev Highlands, Israel - Andrea Junge; Zachary C. Dunseth; Ruth Shahack-Gross; Israel Finkelstein; Markus Fuchs (Archaeological and Anthropological Sciences, 2021)
The Negev Highlands (Israel) are characterized by a rich settlement history over the last millennia. To sustain life in this arid environment, measures to collect and store water were introduced. Two types of installations to collect and store runoff water were built in the region: open reservoirs, and more elaborate subterranean rock-cut cisterns. This article focuses on the latter. Based on a few inscriptions found in rock-cut cisterns, it is assumed that the majority were constructed in the Hellenistic (Nabatean) to Byzantine period. To evaluate this age assessment, this study was carried out at the Borot Hazaz cisterns system, using optically stimulated luminescence (OSL) dating together with micromorphological analyses. Both were applied to sediments that were relocated during the cistern’s construction and usage and after the maintenance activities ended. Despite unfavourable conditions for resetting the OSL signal, including fluvial transport over short distances and sediment deposition by humans in large quantities, it was possible to reconstruct the life cycle of the cistern system. The present study places the construction of the system during the late Roman to Byzantine period, with utilization and long-term maintenance during the following centuries. Maintenance ceased at the Borot Hazaz cistern system gradually over the course of the last 500 years.

Nutrient Pollution and Predation Differentially Affect Innate Immune Pathways in the Coral Porites porites - Katherine E. Dougan; Mark C. Ladd; Corinne Fuchs; Rebecca Vega Thurber; Deron E. Burkepile; Mauricio Rodriguez-Lanetty (Frontiers in Marine Science, 2020)

Genome-wide identification of multifunctional laccase gene family in Eucalyptus grandis: potential targets for lignin engineering and stress tolerance - Mariana L. C. Arcuri; Larissa C. Fialho; Alessandra Vasconcellos Nunes-Laitz; Maria Cecília P. Fuchs-Ferraz; Ivan Rodrigo Wolf; Guilherme Targino Valente; Celso L. Marino; Ivan G. Maia (Trees, 2020)

Combined effects of goethite nanoparticles with metallic contaminants and an organophosphorus pesticide on Eisenia andrei - Marcela I. Cáceres-Wenzel; Julio S. Fuchs; Florencia N. Bernassani; Adriana C. Cochón (Environmental Science and Pollution Research, 2020)

Gene flow and genetic admixture across a secondary contact zone between two divergent lineages of the Eurasian Green Woodpecker Picus viridis - J.-M. Pons; C. Masson; G. Olioso; J. Fuchs (Journal of Ornithology, 2019)

In-situ-Untersuchung von Austenitkornwachstumsprozessen in Stählen mittels Hochtemperatur-Laser-Scanning-Konfokal-Mikroskop - N. Fuchs; C. Bernhard (BHM Berg- und Hüttenmännische Monatshefte, 2019)

The AlpArray Seismic Network: A Large-Scale European Experiment to Image the Alpine Orogen - György Hetényi; Irene Molinari; John Clinton; Götz Bokelmann; István Bondár; Wayne C. Crawford; Jean-Xavier Dessa; Cécile Doubre; Wolfgang Friederich; Florian Fuchs; Domenico Giardini; Zoltán Gráczer; et al. (Surveys in Geophysics, 2018)

Habitat‐driven diversification, hybridization and cryptic diversity in the Fork‐tailed Drongo (Passeriformes: Dicruridae: Dicrurus adsimilis ) - Jérôme Fuchs; Dawie H. De Swardt; Graeme Oatley; Jon Fjeldså; Rauri C. K. Bowie (Zoologica Scripta, 2018)
Species complexes of widespread African vertebrates that include taxa distributed across different habitats are poorly understood in terms of their phylogenetic relationships, levels of genetic differentiation and diversification dynamics. The Fork‐tailed Drongo ( Dicrurus adsimilis ) species complex includes seven Afrotropical taxa with parapatric distributions, each inhabiting a particular bioregion. Various taxonomic hypotheses concerning the species limits of the Fork‐tailed Drongo have been suggested, based largely on mantle and upperpart coloration, but our understanding of diversity and diversification patterns remains incomplete. Especially given our lack of knowledge about how well these characters reflect taxonomy in a morphologically conservative group. Using a thorough sampling across Afrotropical bioregions, we suggest that the number of recognized species within the D. adsimilis superspecies complex has likely been underestimated and that mantle and upperpart coloration reflects local adaptation to different habitat structure, rather than phylogenetic relationships. Our results are consistent with recent phylogeographic studies of sub‐Saharan African vertebrates, indicating that widespread and often morphologically uniform species comprise several paraphyletic lineages, often with one or more of the lineages being closely related to phenotypically distinct forms inhabiting a different, yet geographically close, biome.

Paleolimnological features of a mega-lake phase in the Makgadikgadi Basin (Kalahari, Botswana) during Marine Isotope Stage 5 inferred from diatoms - Mareike Schmidt; Markus Fuchs; Andrew C. G. Henderson; Annette Kossler; Melanie J. Leng; Anson W. Mackay; Elisha Shemang; Frank Riedel (Journal of Paleolimnology, 2017)

Diversification across major biogeographic breaks in the African Shining/Square‐tailed Drongos complex (Passeriformes: Dicruridae) - Jérôme Fuchs; Jon Fjeldså; Rauri C. K. Bowie (Zoologica Scripta, 2017)
Surprisingly, little is known about the extent of genetic structure within widely distributed and polytypic African species that are not restricted to a particular habitat type. The few studies that have been conducted suggested that speciation among African vertebrates may be intrinsically tied to habitat and the dynamic nature of biome boundaries. In the present study, we assessed the geographic structure of genetic variation across two sister‐species of drongos, the Square‐tailed Drongo ( Dicrurus ludwigii ) and the Shining Drongo ( D. atripennis ) , that are distributed across multiple sub‐Saharan biogeographic regions and habitat types. Our results indicate that D. ludwigii consists of two strongly divergent lineages, corresponding to an eastern–southern lineage and a central‐western lineage. Furthermore, the central‐western lineage may be more closely related to D. atripennis , a species restricted to the Guineo‐Congolian forest block, and it should therefore be ranked as a separate species from the eastern–southern lineage. Genetic structure is also recovered within the three primary lineages of the D. atripennis – D. ludwigii complex, suggesting that the true species diversity still remains underestimated. Additional sampling and data are required to resolve the taxonomic status of several further populations. Overall, our results suggest the occurrence of complex diversification patterns across habitat types and biogeographic regions in sub‐Saharan Africa birds.

Erythropoietin production by PDGFR-β+ cells - Katharina Gerl; Karen A. Nolan; Christian Karger; Michaela Fuchs; Roland H. Wenger; Claus C. Stolt; Carsten Willam; Armin Kurtz; Birgül Kurt (Pflügers Archiv - European Journal of Physiology, 2016)

Identification of structural proteins of koi herpesvirus - Walter Fuchs; Harald Granzow; Malte Dauber; Dieter Fichtner; Thomas C. Mettenleiter (Archives of Virology, 2014)

Tectonic and climatic forcing on the rivers in Pamir - Margret C. Fuchs; Richard Gloaguen (International Journal of Earth Sciences, 2013)

Tectonic and climatic forcing on the Panj river system during the Quaternary - Margret C. Fuchs; Richard Gloaguen; Eric Pohl (International Journal of Earth Sciences, 2013)

Holocene river and slope activity in the Visoko Basin, Bosnia‐ H erzegovina – climate and land‐use effects - S. DREIBRODT; C. LUBOS; R. HOFMANN; N. MÜLLER‐SCHEEßEL; I. RICHLING; O. NELLE; M. FUCHS; K. RASSMANN; Z. KUJUNDŽIĆ‐VEJZAGIĆ; H.‐R. BORK; J. MÜLLER (Journal of Quaternary Science, 2013)
Alluvial and colluvial deposits were investigated at prehistoric tells close to the Bosna River. The chronology is based on ten radiocarbon ages, five optically stimulated luminescence ages, and on the archaeological record. Fluvial activity of the Bosna River is indicated by overbank fines [ca. 5000 (±1000) BC , 500 BC until today] and a phase of lateral displacement of the river bed with subsequent channel fills ca. 2000–500 BC . Early Holocene fluvial activity was probably triggered by climatic variability but might have promoted the expansion of Neolithic societies into the Visoko Basin. Mid‐ to late Holocene river activity occurred under increased climatic aridity but coincided with the expansion of prehistoric settlements to a wider area of the river basin on hard rocks in the adjacent mountainous areas. The destruction of the thin soil cover in the mountains is discussed as a probable trigger for enduring subsequent river activity. This is also indicated by a change in the geochemical signature of the alluvial sediments. The proposed mechanism might explain the mid to late Holocene river history in other regions. The potential of geochemical analyses and diachronous high‐resolution archaeological records to make inferences regarding sediment sources and geomorphological processes is demonstrated. Copyright © 2013 John Wiley & Sons, Ltd.

Prospective cohort studies of bowel movement frequency and laxative use and colorectal cancer incidence in US women and men - Xuehong Zhang; Kana Wu; Eunyoung Cho; Jing Ma; Andrew T. Chan; Xiang Gao; Walter C. Willett; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Plasma folate, methylenetetrahydrofolate reductase (MTHFR), and colorectal cancer risk in three large nested case–control studies - Jung Eun Lee; Esther K. Wei; Charles S. Fuchs; David J. Hunter; I-Min Lee; Jacob Selhub; Meir J. Stampfer; Walter C. Willett; Jing Ma; Edward Giovannucci (Cancer Causes & Control, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

A prospective study of intakes of zinc and heme iron and colorectal cancer risk in men and women - Xuehong Zhang; Edward L. Giovannucci; Stephanie A. Smith-Warner; Kana Wu; Charles S. Fuchs; Michael Pollak; Walter C. Willett; Jing Ma (Cancer Causes & Control, 2011)

Generation and characterization of koi herpesvirus recombinants lacking viral enzymes of nucleotide metabolism - Walter Fuchs; Dieter Fichtner; Sven M. Bergmann; Thomas C. Mettenleiter (Archives of Virology, 2011)

The developmental impact of prenatal stress, prenatal dexamethasone and postnatal social stress on physiology, behaviour and neuroanatomy of primate offspring: studies in rhesus macaque and common marmoset - Christopher R. Pryce; Yves Aubert; Claudia Maier; Peter C. Pearce; Eberhard Fuchs (Psychopharmacology, 2011)

Total antioxidant capacity intake and colorectal cancer risk in the Health Professionals Follow-up Study - Rania A. Mekary; Kana Wu; Edward Giovannucci; Laura Sampson; Charles Fuchs; Donna Spiegelman; Walter C. Willett; Stephanie A. Smith-Warner (Cancer Causes & Control, 2010)

Effects of mGluR1 antagonism in the dorsal hippocampus on drug context-induced reinstatement of cocaine-seeking behavior in rats - Xiaohu Xie; Donna R. Ramirez; Heather C. Lasseter; Rita A. Fuchs (Psychopharmacology, 2010)

Evidence for distinct populations of human Merkel cells - A.-C. Eispert; F. Fuchs; J. M. Brandner; P. Houdek; E. Wladykowski; Ingrid Moll (Histochemistry and Cell Biology, 2009)

Primary human coculture model of alveolo-capillary unit to study mechanisms of injury to peripheral lung - Maria Iris Hermanns; Sabine Fuchs; Michaela Bock; Katja Wenzel; Eckhard Mayer; Kai Kehe; Fernando Bittinger; C. James Kirkpatrick (Cell and Tissue Research, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Ecotoxicological assessment of the effects of glyphosate and chlorpyrifos in an Argentine soya field - Norma Casabé; Lucas Piola; Julio Fuchs; María Luisa Oneto; Laura Pamparato; Silvana Basack; Rosana Giménez; Rubén Massaro; Juan C. Papa; Eva Kesten (Journal of Soils and Sediments, 2007)

Process metallurgy for high performance materials at RWTH Aachen/Germany - B. Friedrich; R. Fuchs; C. Kräutlein; C. Lochbichler; A. Lützerath; E. Milke; J. C. Stoephasius (BHM Berg- und Hüttenmännische Monatshefte, 2006)

Development and regulation of monoclonal antibody products: Challenges and opportunities - Wendy C. Weinberg; Michelle R. Frazier-Jessen; Wen Jin Wu; Andrea Weir; Melanie Hartsough; Patricia Keegan; Chana Fuchs (Cancer and Metastasis Reviews, 2005)

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Chronic psychosocial stress in tree shrews: effect of the substance P (NK1 receptor) antagonist L-760735 and clomipramine on endocrine and behavioral parameters - Marieke G. C. van der Hart; Gabriel de Biurrun; Boldizsár Czéh; Nadia M. J. Rupniak; Johan A. den Boer; Eberhard Fuchs (Psychopharmacology, 2005)

Examining SLV-323, a novel NK1 receptor antagonist, in a chronic psychosocial stress model for depression - Boldizsár Czéh; Olga Pudovkina; Marieke G. C. van der Hart; Mária Simon; Urs Heilbronner; Thomas Michaelis; Takashi Watanabe; Jens Frahm; Eberhard Fuchs (Psychopharmacology, 2005)

Differential involvement of the core and shell subregions of the nucleus accumbens in conditioned cue-induced reinstatement of cocaine seeking in rats - Rita A. Fuchs; K. Allison Evans; Macon C. Parker; Ronald E. See (Psychopharmacology, 2004)

Dietary patterns and risk of colon cancer and adenoma in a cohort of men (United States) - Kana Wu; Frank B. Hu; Charles Fuchs; Eric B. Rimm; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2004)

Exploring the method of optical dating and comparison of optical and 14 C ages of Late Weichselian coversands in the southern Netherlands - D. Vandenberghe; C. Kasse; S. M. Hossain; F. De Corte; P. Van Den Haute; M. Fuchs; A. S. Murray (Journal of Quaternary Science, 2004)
A study was made of the applicability of three different techniques for equivalent dose ( D e ) determination in the optical dating of quartz: the single‐aliquot regenerative‐dose technique (SAR), the single‐aliquot additive‐dose technique (SAAD) and the multiple‐aliquot additive‐dose technique (MAAD). For this purpose, quartz grains were extracted from a sequence of Upper Pleniglacial to Late‐glacial coversands exposed at the locality of Ossendrecht in the southwestern Netherlands, a site for which both radiocarbon and earlier luminescence dates are available, providing independent age control. Upon testing the different assumptions underlying each of the three OSL techniques investigated, the SAR protocol was found to be the technique of choice. The optical ages obtained with this protocol were in good agreement with the chronostratigraphical position of the sediments investigated and with the available chronostratigraphical information on the same and equivalent deposits. This confirms the suitability of the SAR technique for dating coversands. Furthermore, a small laboratory intercomparison of SAR‐based D e determinations yielded results that were in fair overall agreement. Copyright © 2004 John Wiley & Sons, Ltd.

Ecotoxicological Characterization of a Disposal Lagoon from a Munition Plant - J. S. Fuchs; M. L. Oneto; N. B. Casabé; O. Gómez Segura; R. Tarulla; M. Vaccarezza; C. Sánchez-Rivas; E. M. Kesten; E. J. Wood (Bulletin of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Lack of Effect of Antibiotic Resistance on Susceptibility of Microorganisms to Chlorhexidine Gluconate or Povidone Iodine - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Presence of Staphylococcus aureus with Reduced Susceptibility to Vancomycin in Germany - G. Bierbaum; K. Fuchs; W. Lenz; C. Szekat; H. -G. Sahl (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Antibacterial Activity of Moxifloxacin (Bay 12-8039) against Aerobic Clinical Isolates, and Provisional Criteria for Disk Susceptibility Tests - S. D. Brown; A. L. Barry; P. C. Fuchs (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

In vitro activity of the new ketolide HMR 3004 compared to an azalide and macrolides againstStreptococcus pneumoniae andHaemophilus influenzae - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Susceptibility testing quality control studies with fosfomycin tromethamine - P. C. Fuchs; A. L. Barry; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

In vitro activity of an orally administered streptogramin (RPR 106,972) compared to quinupristin/dalfopristin and erythromycin - A. L. Barry; P. C. Fuchs; S. D. Brown (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Identification and transcriptional analysis of pseudorabies virus UL6 to UL12 genes - J. M. Dijkstra; W. Fuchs; T. C. Mettenleiter; B. G. Klupp (Archives of Virology, 1997)

Anaerobic metabolism of 2-hydroxybenzoic acid (salicylic acid) by a denitrifying bacterium - C. F. C. Bonting; Georg Fuchs (Archives of Microbiology, 1996)

Anaerobic degradation of m -cresol via methyl oxidation to 3-hydroxybenzoate by a denitrifying bacterium - C. F. C. Bonting; Sabine Schneider; Gü nther Schmidtberg; Georg Fuchs (Archives of Microbiology, 1995)

Anaerobic degradation ofm-cresol via methyl oxidation to 3-hydroxybenzoate by a denitrifying bacterium - Cornelus F. C. Bonting; Sabine Schneider; Günther Schmidtberg; Georg Fuchs (Archives of Microbiology, 1995)

Lithoautotrophic growth of sulfate-reducing bacteria, and description of Desulfobacterium autotrophicum gen. nov., sp. nov. - K. Brysch; C. Schneider; G. Fuchs; F. Widdel (Archives of Microbiology, 1987)

Carbon assimilation by the autotrophic thermophilic archaebacterium Thermoproteus neutrophilus - S. Schfer; C. Barkowski; G. Fuchs (Archives of Microbiology, 1986)

Bacteria and yeasts as possible candidates for the production of inulinases and levanases - A. Fuchs; J. M. de Bruijn; C. J. Niedeveld (Antonie van Leeuwenhoek, 1985)